Pengaruh Pembelajaran Mata Pelajaran Produk Kreatif dan Kewirausahaan Terhadap Minat Berwirausaha Siswa Akuntansi di SMK Negeri 1 Bantaeng - Dewi, Sasmita; Azis, Muhammad; Nuraisyiah (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2025)
This study aims to analyze the effect of learning creative products and entrepreneurship subjects on the entrepreneurial interest of class XI Accounting students at SMK Negeri 1 Bantaeng. The type of research used is descriptive research using a quantitative approach. Data were collected using a questionnaire. Data were analyzed using regression analysis. The results of this study indicate that learning creative products and entrepreneurship is in the very good category, with an average percentage of 82.3% and entrepreneurial interest is in the very good category, with an average percentage of 85.1%. The results of the analysis it shows that learning creative products and entrepreneurship has a positive effect on entrepreneurial interest.